217k views
0 votes
The sum of n terms of 1^ 2 ,3^ 2 ,5^ 2 ,7^ 2 ,...., is (b) (n / 2)(4n ^ 2 - 1) a)(n/3)(4n^ 2 -1)​

User Spindoctor
by
5.2k points

1 Answer

2 votes

Explanation:

We're asked to find the simplified form of,


\longrightarrow S=\underbrace{1^2+3^2+5^2+7^2+\,\dots}_{\textrm{$n$ terms}}

The n'th term of the sequence
1^2,\ 3^2,\ 5^2,\ 7^2,\,\dots is
(2n-1)^2. So,


\longrightarrow S=1^2+3^2+5^2+\,\dots\,+(2n-1)^2

We know the following sum,


\longrightarrow 1^2+2^2+3^2+\,\dots\,+n^2=(n(n+1)(2n+1))/(6)

This is expression for the sum of squares of first 'n' natural numbers. In case of '2n' natural numbers,


\longrightarrow 1^2+2^2+3^2+\,\dots\,+(2n)^2=(2n(2n+1)(4n+1))/(6)

We separate odd squares and even squares in the LHS.


\begin{aligned}\longrightarrow\ \ &\Big(1^2+3^2+5^2+\,\dots\,+(2n-1)^2\Big)&\\+\ \ &\Big(2^2+4^2+6^2+\,\dots\,+(2n)^2\Big)&=(2n(2n+1)(4n+1))/(6)\end{aligned}

We can take 4 common from the sum of even squares.


\begin{aligned}\longrightarrow\ \ &\Big(1^2+3^2+5^2+\,\dots\,+(2n-1)^2\Big)&\\+\ \ &4\Big(1^2+2^2+3^2+\,\dots\,+n^2\Big)&=(2n(2n+1)(4n+1))/(6)\end{aligned}

Now the sums in LHS are, as written above,


1^2+3^2+5^2+\,\dots\,+(2n-1)^2=S


1^2+2^2+3^2+\,\dots\,+n^2=(n(n+1)(2n+1))/(6)

So,


\longrightarrow S+(4n(n+1)(2n+1))/(6)=(2n(2n+1)(4n+1))/(6)


\longrightarrow S=(2n(2n+1)(4n+1))/(6)-(4n(n+1)(2n+1))/(6)


\longrightarrow S=(2n+1)/(6)\Big[2n(4n+1)-4n(n+1)\Big]


\longrightarrow S=(2n+1)/(6)\Big[4n^2-2n\Big]


\longrightarrow S=(2n(2n-1)(2n+1))/(6)


\longrightarrow\underline{\underline{S=(n)/(3)\,(4n^2-1)}}

This is the expression for the sum of squares of first 'n' odd natural numbers.

User Helfer
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.